Social justice in these times - O'Donnell, James, 1951-; Pruyn, Marc; Chávez, Rudolfo Chávez, 1951- (International social studies forum, the series., 2004)
Thirteen contributions from academics representing a variety of disciplines confront issues relating to social justice in a post-9/11 world. Sample topics include the politics of coalition building among progressive educators and the role of participatory democracy in the critical praxis of social justice.